Implementation of ERP module for the key processes of hull production in shipbuilding industry (International Journal of Engineering and Computer Science, 2018)
Enterprise Resource Planning (ERP) is the strong tool in the hands of management for taking timely and accurate decisions during the execution of projects. It also enables organization competitively for value addition, cost reduction and improvement. At present context, ERP has become common requirement of any organizational excellence model.ERP has several modules like Customer requirement module, finance and accounts, materials, projects, manufacturing, quality, welding and services.